Diabetes Distress and Self-Care Activities Among Patients With Diabetes Type II: A Correlation Study - Aziza Ibrahim Abd El Kader PhD; Mishmisha Elsayed Ibrahim PhD; Helalia Shalabi Mohamed PhD; Basma Mohamed Osman PhD (SAGE Publishing, 2023)
Introduction Diabetes mellitus (DM) is a main, highly prevalent, and challenging public health issue. Suboptimal self-care for type II diabetes can lead to poor glycemic control, complications, and even death. Objective This study investigated the incidence of distress and its link with self-care habits of patients with diabetes type II. Methods A correlational, cross-sectional design with a convenient sample of 200 patients was used to conduct this study. Three questionnaires were administered: (A) the demographic and medical data questionnaire; (B) diabetes self-care activities in brief; and (C) the diabetes distress scale in Arabic language. Results The patients' mean age was 51.78 ± 11.34; 80% of patients practiced lower levels of diabetes self-care, and 37% of them had a high level of diabetes distress. Self-care is associated with diabetes distress ( R  = −0.152, p -value = .032). Conclusion Self-care activities can help in the early detection and management of diabetes distress. Sustained self-care education is promising to minimize diabetes distress. The potential advantages of association between diabetes distress and self-care can offer self-care programs that enhance diabetes distress management.